2015
DOI: 10.12911/22998993/2802
|View full text |Cite
|
Sign up to set email alerts
|

Biochar to Improve the Quality and Productivity of Soils

Abstract: 75% of the area of Poland is covered by dystric, brunic, luvic and albic soils, with only <1% of total surface covered by very good soils i.e. chernozems [Skłodowski, Bielska, 2009]. It is necessary to fertilize poor soils in order to use them effectively. Soil quality is improved in Poland through liming (control of chemical reaction), enrichment of sorption complex, introduction of the organic substance (peat, brown coal, organic fertilizers) or through enrichment of loamy fraction (soil loaming, synthetic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 1 publication
2
12
0
Order By: Relevance
“…These conclusions are consistent also with the results of research on impact of a woody BioC on properties of a sandy loam soil and spring barley 50 , which demonstrated that BioC has a long-term effect, noticeable only a few years after its application to the soil. The effect of carboxylic groups of BioC is interesting because BioC production by biomass pyrolysis results in the partial degradation of oxygen-containing functional groups 51 , 52 . No similar changes were observed in the distribution of dissociation constants of grassland amended with BioC (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These conclusions are consistent also with the results of research on impact of a woody BioC on properties of a sandy loam soil and spring barley 50 , which demonstrated that BioC has a long-term effect, noticeable only a few years after its application to the soil. The effect of carboxylic groups of BioC is interesting because BioC production by biomass pyrolysis results in the partial degradation of oxygen-containing functional groups 51 , 52 . No similar changes were observed in the distribution of dissociation constants of grassland amended with BioC (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The feedstock was transported along the retort via a steel screw conveyor which allowed for easy and simple adjustment and control of the feedstock residence time and its transport velocity within the retort. The control of these parameters was crucial for the production of biochar with the desired parameters (carbon content and porosity) [ 32 ]. The pyrolysis process of the sunflower husk was carried out at inert atmosphere with no external gas at 650 °C for roughly 15 min.…”
Section: Methodsmentioning
confidence: 99%
“…After measurement of fresh biomass weight of individual plants (2 plants from each pot), the biomass was dried (105 °C for 1 h). The analysis of plant biomass was made according to Polish Standard PN-G-04560:1998P [29].…”
Section: Experimental Plan Soil Material Organic and Inorganic Amenmentioning
confidence: 99%